Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Disiplin Guru dengan Kepemimpinan sebagai Variabel Intervening - Meilisa Dewi Putri (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to examine how much influence Organizational Culture and Organizational Commitment have on the Discipline of State Vocational High School Teachers in Padang Timur District with Leadership as an Intervening variable. The method of collecting data is through surveys and distributing questionnaires, with a sample of 94 respondents. The analytical method used is path analysis using smartpls. The results obtained based on the Partial Test have a significant positive effect on Organizational Culture on Leadership. There is an insignificant positive effect of Organizational Commitment on Leadership. There is a significant positive influence of Organizational Culture on Teacher Discipline. There is an insignificant positive effect of Organizational Commitment on Teacher Discipline. There is a significant positive effect of Leadership on Teacher Discipline. Leadership mediates the influence of Organizational Culture on Teacher Discipline. Leadership does not mediate the effect of Organizational Commitment on Teacher Discipline.